Attitudes of Physical Therapy students to Computer-Assisted Instruction - Alviar, Nomar M.
The benefits of computer-assisted instruction are more assured if users possess a sustained positive acceptance of the instructional medium. This study explored the factors that influence health professions students' attitudes to computer-assisted instruction using Davis' Technology Acceptance Model as the major grounding framework. Attitudes to computers and computer-assisted instruction were elicited from a sample of 63 physical therapy students of Pamantasan ng Lungsod ng Maynila who made use of a computer-based self-instructional module on cell structure and function. Positive attitudes to computer-assisted instruction were expressed by all respondents across socio-demographic groups and learning style preferences. These attitudes were significantly influenced by positive attitude towards computers and generated a considerably greater intent among physical therapy students to make use of computer-assisted instruction.